Characterization of the Electron Beam in the ACHIP Chamber in SwissFEL. (July 2020) - Ischebeck, Rasmus; Bettoni, Simona; Borrelli, Simona; Calvi, Marco; Dijkstal, Philipp; Ferrari, Eugenio; Guzenko, Vitaliy; Hauenstein, Dominique; Hermann, Benedikt; Hürzeler, Orell; Kittel, Christoph; Lombosi, Csaba; et al.
Abstract: We have installed an interaction chamber in the electron beam line of SwissFEL. Electrons with a particle energy of 3 GeV are focused to a few-micrometer beam size. Samples placed in this beam can be aligned to the electron beam with a hexapod. The goal of this installation is to demonstrate laser-driven acceleration inside dielectric structures. We present here the layout of this interaction chamber as well as first measurements with the electron beam.